Household Food Insecurity Status and Determinants: The Case of Botswana and South Africa - Simbarashe Ndhleve; Clarah Dapira; Hlekani Muchazotida Kabiti; Zibongiwe Mpongwana; Elphina Nomabandla Cishe; Motebang Dominic Vincent Nakin; Stephen Shisanya; Keitirele Patricia Walker (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
This study used a survey questionnaire to investigate the state and determinants of household food security in South Africa and Botswana. In South Africa, 1557 households in two District Municipalities within Eastern Cape Province participated in the study. In Botswana, data was collected from 506 in Southern Kanye, southeast District, and Gaborone households. The paper employed Household Food Insecurity Access Scale and Prevalence to investigate the state food security across the sample population. The Household Food Insecurity Access Prevalence was used to determine the characteristics of and changes in household food insecurity of the sample households. The linear and ordinal regression analyses were carried out to outline determinants of food insecurity in the region. Findings emanating from the current study show a high prevalence of food insecurity in both countries. Meanwhile, geographical location, household size, and socio-economic infrastructure emerged as common determinants of food security for Botswana and South Africa. The paper recommends state-mediated intervention to improve access to basic socio-economic infrastructure and address unemployment rates in both countries as key areas to improve food security status.